Exploring the Psychometrical Properties of Achievement Goals in Indonesian College Students - Siti Dini Fakhriya; Jesyia Meyrinda; Tsurayya Syarif Zain; Mellisa Kurnia Asfitri (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
Achievement Goals Theory (AGT) is focused on individuals’ motivation and goal-pursuit behavior to achieve attainable targets. Therefore, this study aimed to investigate the validity and reliability of the AGT scale among Indonesian college students. Participants in this study included 220 students sampled using non-probability sampling. The Elliot’s Achievement Goals Questionnaire-Revised (AGQ-R) was used to measure participants’ beliefs about mastery-goal, mastery-avoidance, performance-goal, and performance-avoidance goals with three items on each subscale. Concurrent validity, Confirmatory Factor Analysis (CFA) and Rasch measurement model were carried out. Subsequently, Cronbach's Alpha, composite reliability were used to test reliability. The result showed that the three-factor model was the most appropriate representation as goodness of fit indexes ?2 (166) = 202.498, p = .0000, RMSEA = 0.045, 90% CI = 0.051? 4.493, probability RMSEA = 2.227, CFI =1.000, TLI = 1.000, SRMR = 0.056. AGQ-R was shown to be a valid and reliable instrument to be used on students in Indonesia. The three-factor model was the most appropriate representation, as well as a valid and reliable instrument to measure achievement goals in the sample of students in Indonesia. This model consisted of mastery and performance goals, while mastery-avoidance and performance-avoidance were combined into one domain. This validated psychometric instrument use to assess student motivation and design culturally-aligned interventions in the higher education and allow a development for teaching strategies that support student engagement and academic success.